THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY, THE NUMBER OF BOARD OF DIRECTORS, AND SIZE OF COMPANIES ON STOCK PRICES WITH PROFITABILITY AS INTERVENING VARIABLES IN LISTED COMPANIES IN JAKARTA ISLAMIC INDEX 2013-2016 PERIOD - yenny, yenny (International Journal of Public Budgeting, Accounting and Finance, 2018)
This study aims to empirically examine the effect ofCorporate Social Responsibility(CSR), number of board of directors, and company size on profitability proxied by ROA (Return On Assets) and stock prices on companies listed in the Jakarta Islamic Index during the period 2013-2016 .The next objective is to examine whether profitability is able to mediate CSR relationships, the number of directors, and the size of the company on stock prices. In this study the sample used was a company registered in the Jakarta Islamic Index (JII) during the period 2013-2016, there were 15 sample companies that remained consistently registered on the JII.The sampling method is census method, so the total observation of the research is 60. The data analysis technique used in this research is multiple linear regression analysis with SPSS. The results showed thatCSR had a positive and significant effect on profitability, the number of directors had a positive and insignificant effect on profitability, and the size of the company had a negative and significant effect on profitability.The results of subsequent studies, namely CSR have a positive and insignificant effect on stock prices, the number of directors has a positive and significant effect on stock prices, the size of the company has a negative and insignificant effect on stock prices, and profitability has a negative and significant effect on stock prices.For testing the intervening variable (profitability) obtained results that: profitability is able to mediate CSR relations and company size to stock prices, while profitability is not able to mediate the relationship of the number of godsand directors to stock prices.